1988
DOI: 10.1111/j.1469-8137.1988.tb03724.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance in natural populations of Trifolium repens L.

Abstract: SUM iVl ARYThe salt tolerances of plants from tiatural populations of Trifolium repens L, (White Clover) growing in saline and non-saline sites were compared by root growth tests at a range of NaCl coticentrations. Platits from three saltmarsh sites showed high or very high salt tolerance, with relatively vigorous root growth in 150-200 mM NaCl, Plants with two non-saline inland sites showed little or no tolerance, A sea-clifF population and plants of cv, Gwenda showed intermediate levels of tolerance at low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
2
11
1
Order By: Relevance
“…Other studies on maritime and inland populations of A. stolonifera L. (Tiku & Snaydon, 1971 ;Kik, 1989) and Trifolium repens L. (Ab-Shukor et al., 1988) confirmed this observation. However, only Tiku & Snaydon (1971) took quantitative measurements of the salinities of the sites from w-hich populations were collected.…”
Section: Relative Tolerance Of Accessionssupporting
confidence: 55%
“…Other studies on maritime and inland populations of A. stolonifera L. (Tiku & Snaydon, 1971 ;Kik, 1989) and Trifolium repens L. (Ab-Shukor et al., 1988) confirmed this observation. However, only Tiku & Snaydon (1971) took quantitative measurements of the salinities of the sites from w-hich populations were collected.…”
Section: Relative Tolerance Of Accessionssupporting
confidence: 55%
“…The existence of salt tolerant populations has been recognized in several species (e.g. Ab-Shukor et al 1988;Bowman 1988;Hannon & Bradshaw 1968;Kik 1989). The relative salt tolerance of these populations to increasing NaC1 in the root medium is positively correlated with the salinity of their native soils.…”
Section: Introductionmentioning
confidence: 98%
“…Types C, D, and E also showed differences in growth rate, with the more tolerant types (such as E) showing more rapid growth (Table 3). Usually, tolerant species or individual genotypes are related with low-degree damages in early plant growth and vegetative organs (Ahmad & Wainwright, 1976;Humphreys, 1982;Shannon, 1984;Ab-Shukor et al, 1988;Wang et al, 1997;Kik, 1989;Bayuelo-Jiménez et al, 2002;Mguis et al, 2008;Lee et al, 2009). In this study, all 88 E-type lines that survived to maturity could be regarded as having high salinity tolerance.…”
Section: Discussionmentioning
confidence: 89%
“…The seed weight was the second trait with smaller variation. Ab-Shukor et al, (1988) reported that populations of Trifolium repens L. growing in salt-marsh sites showed highly salt-tolerant root growth, and the non-saline inland population had no such tolerance. Kik (1989) observed that genotypes that do not have maximal salt resistance remained within a salt marsh population of Agrostis stolonifera L. The coastal population of wild soybean in the present study clearly exhibited high levels of heterogeneity in salinity tolerance, which was reflected by different survival times of individual lines (Tables 1 and 2), and greater variation in characters and different D values among these E-type lines (Table 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation